Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Immune gene regulation is associated with age and environmental adversity in a nonhuman primate - Marina M. Watowich; Christina E. Costa; Kenneth L. Chiou; Elisabeth A. Goldman; Rachel M. Petersen; Sam Patterson; Melween I. Martínez; Kirstin N. Sterner; Julie E. Horvath; Michael J. Montague; Michael L. Platt; Lauren J. N. Brent; et al. (Molecular Ecology, 2024)
Phenotypic aging is ubiquitous across mammalian species, suggesting shared underlying mechanisms of aging. Aging is linked to molecular changes to DNA methylation and gene expression, and environmental factors, such as severe external challenges or adversities, can moderate these age‐related changes. Yet, it remains unclear whether environmental adversities affect gene regulation via the same molecular pathways as chronological, or ‘primary’, aging. Investigating molecular aging in naturalistic animal populations can fill this gap by providing insight into shared molecular mechanisms of aging and the effects of a greater diversity of environmental adversities – particularly those that can be challenging to study in humans or laboratory organisms. Here, we characterised molecular aging – specifically, CpG methylation – in a sample of free‐ranging rhesus macaques living off the coast of Puerto Rico ( n samples = 571, n individuals = 499), which endured a major hurricane during our study. Age was associated with methylation at 78,661 sites (31% of all sites tested). Age‐associated hypermethylation occurred more frequently in areas of active gene regulation, while hypomethylation was enriched in regions that show less activity in immune cells, suggesting these regions may become de‐repressed in older individuals. Age‐associated hypomethylation also co‐occurred with increased chromatin accessibility while hypermethylation showed the opposite trend, hinting at a coordinated, multi‐level loss of epigenetic stability during aging. We detected 32,048 CpG sites significantly associated with exposure to a hurricane, and these sites overlapped age‐associated sites, most strongly in regulatory regions and most weakly in quiescent regions. Together, our results suggest that environmental adversity may contribute to aging‐related molecular phenotypes in regions of active gene transcription, but that primary aging has specific signatures in non‐regulatory regions.

Effects of early life adversity on maternal effort and glucocorticoids in wild olive baboons - Sam K. Patterson; Katie Hinde; Angela B. Bond; Benjamin C. Trumble; Shirley C. Strum; Joan B. Silk (Behavioral Ecology and Sociobiology, 2021)